Advances in dental bioengineering and their application in orthodontics and dento - Caicedo, Clara Johana; Villareal, Maria Paula (Revista Estomatología, 2017)
The advances in dental bioengineering disclose the importance of genetic, cellular and tissue therapies as the latest approach to the regenerative medicine for biomechanical orthodontic and dentofacial orthopedics; extending its scope, correcting structural flaws and offering biological alternatives with high quality technology for specialist practices. In this review, some recent findings related to genetic advances in dental bioengineering are provided and applied to the induction of the potential cell forming in the craniofacial complex and its clinical applications. A special research was made using some databases such as: Scopus, Medline and Science Direct, with the following keywords: Bioengineering, Stem cells, and Gen therapy. Finally, we can conclude that the focus of dental practice is led to regenerative medicine as a conventional, innovative and high quality therapy, giving closely results to natural human biology, long term effectivity and less adverse effects. Then we can scope out the vision of all clinic procedures limits with all patients.